Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fmicb.2018.02406
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Dissection of the Lytic Replication Cycles of Herpes Simplex Viruses in vitro

Abstract: Herpes simplex viruses type 1 and type 2 (HSV-1 and HSV-2) produce lifelong infections and are highly prevalent in the human population. Both viruses elicit numerous clinical manifestations and produce mild-to-severe diseases that affect the skin, eyes, and brain, among others. Despite the existence of numerous antivirals against HSV, such as acyclovir and acyclovir-related analogs, virus variants that are resistant to these compounds can be isolated from immunosuppressed individuals. For such isolates, second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 214 publications
(277 reference statements)
1
42
0
Order By: Relevance
“…2 and 3). It is well known and documented that the expression levels of late genes do not peak until much later during infection (17,26,44,45). These observations suggest that recruitment of Pol II to ␥ gene promoters through the activities of HSV-1 ␣ gene products cannot fully account for the robust transcription of late genes after 6 hpi (Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…2 and 3). It is well known and documented that the expression levels of late genes do not peak until much later during infection (17,26,44,45). These observations suggest that recruitment of Pol II to ␥ gene promoters through the activities of HSV-1 ␣ gene products cannot fully account for the robust transcription of late genes after 6 hpi (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…This comparison required temporal assignment of genes. For 31 genes, the temporal designations were agreed upon in multiple reports (7,17,24,26,28,44,66). When the remaining genes were examined for temporal class designation, we noted that many of the genes that were designated ␥ 1 or ␥ 2 genes by immunoblotting were designated ␤ genes by transcriptional analysis through either microarray or Northern blot experiments (26,28,44,45,66).…”
Section: (Continued On Next Page)mentioning
confidence: 99%
“…Firstly, we explored the anti-HSV-2 effects of JZ-1, penciclovir and berberine at 6 h, 12 h, 18 h, and 24 h of treatment. Immunofluorescence microscopy analysis of gD expression showed that only JZ-1 had an antiviral effect at the treatment of 6 h. Since the late gene transcription products of HSV-2, including gB, gC, gD, gE, gG, and other viral structural proteins, are produced significantly 12-15 h after infection (Ibáñez et al, 2018;Su et al, 2017), the gD observed in host cells at 6 h of infection was mostly derived from the original virons that infected the cells, suggesting that JZ-1 plays a vital role in the early Fig. 5.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the possibility that the algae extracts block the ability of the viruses to bind to the cell surface, we evaluated the amount of HSV particles bound to the surface of HeLa cells inoculated with the viruses at 4°C, by determining the amount of glycoprotein B and glycoprotein D present in the cells after an incubation period of 5 h at this temperature ( Ibáñez et al, 2018 ). As shown in Figure 6A , the treatment with the M. pyrifera extract decreased the amount of HSV-2 bound to the cell surface.…”
Section: Resultsmentioning
confidence: 99%